KAJIANYURIDIS TERHADAP BERALIHNYA KEWENANGAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DARI PEMERINTAH PUSAT KEPADA PEMERINTAH DAERAH KABUPATEN SERDANG BEDAGAI - ALBERT LODEWYK SENTOSA SIAHAAN (PREMISE LAW JURNAL, 2015)
By the imposition of Regional Regulation of Serdang Bedagai District No. 1/2012 on Tax on Rural and Urban Land and Building, the authority to collect it was transferred from the central government to Deli Serdang District Administration. The tariff in the Regional Regulation of Deli Serdang District No. 1/2012 on Tax on Land and Building had met the principle of justice vertically ands horizontally because it differentiates the imposition of tax on taxpayers based on NJOP (0.1% and 0.2%) and the same tax on the same NJOP. Legal remedy on delinquent taxes of PBB P2 before the transfer occurred was that Deli Serdang District Administration became the authority to bill the delinquent taxes of PBB P2 by using, if possible, Warrant according to Law No. 19/2000 as the amendment of Law No. 19/1997. Keywords: Transfer of Authority, Rural and Urban Tax on Land and Building